Environmental engineering and management - Dhameja, Suresh K (S. K. Kataria, 2006)
Environmental engineering and management / Dhameja, Suresh K. -- Delhi: S. K. Kataria, 2006 628 D533e2 2nd ed. No. of Copies : 3